The Effect of Employee Well-Being and Work Motivation on Organizational Citizenship Behavior Among Employees at PT Hui Shun Indonesia (HSI) - Irma Sulasih; Lisa Harry Sulistiyowati (Universitas KH. Abdul Chalim Mojokerto, 2026)
This study aims to examine the partial and simultaneous effects of employee well-being and work motivation on Organizational Citizenship Behavior (OCB) among employees of PT Hui Shun Indonesia (HSI). The population of this study consisted of all 150 employees of PT Hui Shun Indonesia. A saturated sampling technique was employed, whereby the entire population was used as the research sample. Data were collected through questionnaires and analyzed using multiple linear regression analysis. The results indicate that employee well-being has a positive and significant effect on Organizational Citizenship Behavior, with a significance value of 0.000 (< 0.05). Meanwhile, work motivation does not have a significant partial effect on Organizational Citizenship Behavior, with a significance value of 0.105 (> 0.05). However, employee well-being and work motivation simultaneously have a significant effect on Organizational Citizenship Behavior, as indicated by a significance value of 0.000 (< 0.05). The coefficient of determination shows that employee well-being and work motivation jointly explain 43.1% of the variance in Organizational Citizenship Behavior, while the remaining 56.9% is influenced by other variables not included in this study. These findings provide practical implications, suggesting that improving employee well-being can encourage extra-role behaviors that contribute to enhanced organizational performance, productivity, and competitiveness, thereby supporting economic growth and development through the strengthening of human resource quality.